An experimental study of air quality inside large athletic halls - Stathopoulou, O.I.a; Assimakopoulos, V.D.b; Flocas, H.A.a; Helmis, C.G.a (Building and Environment, 2008)
Air quality in two large athletic halls with different ventilation (natural and mechanical) was investigated in relation to outdoor pollution and meteorological conditions. Simultaneous measurements of O3, NO, NO2 and SO2 were performed in the halls at two heights (at the arena and spectators’ seats) and outdoors. BTX concentrations at the spectators’ seats and outdoor NMHCs, CH4, PM10 and CO concentrations were also measured. Analysis of diurnal variations of the pollutants’ concentrations, cross correlation analysis of the concentration time-series and principal component analysis were applied to the collected data. Results revealed that outdoor pollution significantly affected indoor air quality of both halls. However, this effect was different for the two buildings, depending on the ventilation types, the wind direction prevailing at the areas and the kind of indoor activity recorded. It was found that the latter parameters controlled the pollutants concentration levels in the halls and their response to the changes of the outdoor pollution levels. Temperature and pollution stratification enhancing during athletic events were also evident in both halls but with different characteristics observed, such as the spatial distribution of the indoor pollutants. The airflow patterns prevailing in each hall, imposed by the ventilation operation schemes were important factors. © 2007 Elsevier Ltd. All rights reserved.
cited By (since 1996)11
Keywords: Air quality; airflow; Airflow patterns; Athletic halls; Atmospheric chemistry; Atmospheric composition; atmospheric pollution; building; experimental study; Indoor air pollution; Indoor air quality; Pollution stratification; principal component analysis; sports facility; time series analysis; Ventilation